Measuring Governance: Developing a Novel Metric for Assessing Whether Policy Environments are Conducive for the Development and Implementation of Nutrition Interventions in Nepal - Grace Namirembe; Robin Shrestha; Patrick Webb; Robert Houser; Dale Davis; Kedar Baral; Julieta Mezzano; Shibani Ghosh (Kerman University of Medical Sciences, 2022)
BackgroundThe Nutrition Governance Index (NGI) defines a first standardized approach to quantifying the 'quality of governance' in relation to national plans of action to accelerate improvements in nutrition. It was created in response to growing demand for evidence-based measures that reveal opportunities and challenges as nutrition-related policies on paper are translated into outcomes on the ground. Numerous past efforts to measure 'governance,' most notably World Health Organization's (WHO's) NGI and the separate Hunger and Nutrition Commitment Index (HANCI), both of which lack granularity below the national level and each of which fails to capture pinch points related to necessary crosssectoral actions. This paper addresses such caveats by introducing an innovative metric to assess self-reported practices of, and perceptions held by, administration officials tasked with implementing government policy at the sub-national level. The paper discusses the development of this metric, its methodology, and explores its application in the context of Nepal. MethodsConducted as part of a nationally representative longitudinal survey across 21 of Nepal's 75 districts, the substudy on which this paper is based used data from 520 government and non government officials at different geographic and administrative tiers of authority. Using robust statistical techniques, structured questionnaire data were condensed into a score using a scale from 0 to 100. ResultsSix domains were identified through the analysis: Understanding Nutrition and related responsibilities; Collaboration; Financial Resources; Nutrition Leadership, Capacity, and Support. About half of all health sector representatives achieved a high score (>3 on 5-point scale) compared to representatives in other sectors of government activity (such as agriculture or education) (χ2= 12.99, P < .003). The health sector also showed the most improvement in mean NGI score over a two-year follow-up period.ConclusionThis paper shows that self-reported perceptions and behaviors of those responsible for policy implementation can be usefully quantified. The NGI can be used to assess countries' readiness for the application of nutrition policies.